1994
DOI: 10.1172/jci117562
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular perfusion is impaired in a rat model of normotensive sepsis.

Abstract: We hypothesized that normotensive sepsis affects the ability of the microcirculation to appropriately regulate microregional red blood cell (RBC) flux. An extensor digitorum longus muscle preparation for intravital study was used to compare the distribution of RBC flux and the functional hyperemic response in SHAM rats and rats made septic by cecal ligation and perforation (CLP). Using intravital microscopy, we found that sepsis was associated with a 36% reduction in perfused capillary density (from 35.3±+1.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
209
1
12

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(235 citation statements)
references
References 31 publications
(26 reference statements)
13
209
1
12
Order By: Relevance
“…21 Normotensive sepsis induces absence of capillary flow 22 and alters leukocyte-endothelium interactions. 19,23,24 Smalley et al 24 found that CLP significantly increases leukocyte adherence and infiltration into the upper gastrointestinal tract 4 hours after intervention.…”
Section: Discussionmentioning
confidence: 99%
“…21 Normotensive sepsis induces absence of capillary flow 22 and alters leukocyte-endothelium interactions. 19,23,24 Smalley et al 24 found that CLP significantly increases leukocyte adherence and infiltration into the upper gastrointestinal tract 4 hours after intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with sepsis show reductions in the proportion of perfused capillaries,53 and in animal models of normotensive sepsis, the density of capillaries with either intermittent or no flow is elevated, while the normal response to vasodilators is reduced 54, 55. Notably, death from MOF after septic shock is antedated by reductions in the proportion of perfused sublingual capillaries compared to survivors, in spite of identical systemic hemodynamic and oxygenation variables 56.…”
Section: Evidence Of Changes In Capillary Density and Cth From Directmentioning
confidence: 99%
“…Several trials in which OPS was used to evaluate microcirculation in sepsis were recently published ( (2) 1994 J Clin Invest.…”
Section: Evidence Of Septic Microcirculatory Changesmentioning
confidence: 99%
“…(2)(3)(4) During this period of research, human studies were dependent upon the large microscopes that were used for periungual microcirculation assessments. These assessments showed a reduced rate of capillary flow in normotensive patients with fever.…”
Section: Introductionmentioning
confidence: 99%